2015
DOI: 10.1016/j.neuint.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Butyrylcholinesterase: K variant, plasma activity, molecular forms and rivastigmine treatment in Alzheimer's disease in a Southern Brazilian population

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder in which there is a decline of cholinergic function. The symptomatic AD treatment involves the use of ChEIs (cholinesterase inhibitors) as rivastigimine, a dual inhibitor. The human butyrylcholinesterase (BChE) is an enzyme that has specific roles in cholinergic neurotransmission and it has been associated with AD. In the serum, BChE is found in four main molecular forms: G1 (monomer); G1-ALB (monomer linked to albumin); G2 (dimer); and G4 (tetramer). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 62 publications
(73 reference statements)
0
17
0
Order By: Relevance
“…Multiple regression analyses confirmed that AD acts as the main factor in plasma BuChE activity reduction and severe stages are related with an even greater reduction (20). These findings suggest that the reduction of plasma BuChE in AD patients is most likely associated with a feedback mechanism and provides a future potential of using this enzyme as a possible secondary marker for AD (20).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Multiple regression analyses confirmed that AD acts as the main factor in plasma BuChE activity reduction and severe stages are related with an even greater reduction (20). These findings suggest that the reduction of plasma BuChE in AD patients is most likely associated with a feedback mechanism and provides a future potential of using this enzyme as a possible secondary marker for AD (20).…”
Section: Discussionmentioning
confidence: 60%
“…Multiple regression analyses confirmed that AD acts as the main factor in plasma BuChE activity reduction and severe stages are related with an even greater reduction (20). These findings suggest that the reduction of plasma BuChE in AD patients is most likely associated with a feedback mechanism and provides a future potential of using this enzyme as a possible secondary marker for AD (20). A study in middle-aged or elderly men and women (50 years or older) reported that individuals in the lowest quintile of BuChE activity had significantly higher mortality than those in the highest quintile [HRs (95% CI): all-cause mortality, 1.62 (1.15-2.30); cardiovascular deaths, 1.79 (1.05-3.05)] after adjusted for other predictors of mortality by Cox regression methods (21).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…These drugs are used to treat patients with mild-to-moderate AD 128 . BChE has a specific role in cholinergic neurotransmission and it has been associated with AD 129 . Individual ChEIs differ from each other with respect to their pharmacologic properties.…”
mentioning
confidence: 99%
“…The human body contains ten times more BChE than AChE 132 . It was reported that in AD, AChE is lost up to 85% in specific brain regions, whereas BChE levels rise with disease progression 129,133 . It was also shown that the main AChE inhibitory effect was primarily associated with aromatic compounds and, to a lesser degree, with aliphatic compounds 134 .…”
mentioning
confidence: 99%